Chlorobutanol, a Preservative of Desmopressin, Inhibits Human Platelet Aggregation and Release In Vitro - Chen, Shih-Luen; Yang, Wu-Chang; Huang, Tung-Po; Wann, Shiang; Teng, Che-ming (Thrombosis and Haemostasis, 1990)
Therapeutic preparations of desmopressin for parenteral use contain the preservative chlorobutanol (5 mg/ml). We show here that chlorobutanol is a potent inhibitor of platelet aggregation and release. It exhibited a significant inhibitory activity toward several aggregation inducers in a concentration- and time-dependent manner. Thromboxane B2 formation, ATP release, and elevation of cytosolic free calcium caused by collagen, ADP, epinephrine, arachidonic acid and thrombin respectively were markedly inhibited by chlorobutanol. Chlorobutanol had no effect on elastase- treated platelets and its antiplatelet effect could be reversed. It is concluded that the antiplatelet effect of chlorobutanol is mainly due to its inhibition on the arachidonic acid pathway but it is unlikely to have a nonspecitic toxic effect. This antiplatelet effect of chlorobutanol suggests that desmopressin, when administered for improving hemostasis, should not contain chlorobutanol as a preservative.